Preschool Availability and Female Labor Force Participation : Evidence from Indonesia - Halim, Daniel; Johnson, Hillary C.; Perova, Elizaveta (World Bank, Washington, DC, 2019)
At 50.9 percent, female labor force participation in Indonesia is far below the regional average of 60.8 percent. Is it being hindered by a lack of affordable childcare services in the country? This paper exploits the joint variations in preschool age eligibility and access to preschool across regions and over years in a difference-in-difference-in-differences framework. With a longitudinal survey that tracks individuals for an average of 22 years, a panel of mothers was constructed to estimate the elasticity of maternal employment to preschool access. The analysis finds that an additional public preschool per 1,000 children increases the work participation of mothers of preschool age eligible children by 11-16 percent from the baseline mean. Private preschools do not increase work participation at the extensive margin, but they increase the likelihood of holding a second job. The availability of preschools induces mothers to informal sector occupations that do not require full-time commitments.